PERMIAN OF THE RUSSIA AND CIS AND ITS INTERREGIONAL CORRELATION - Kotlyar G.V. (My University, 2000)
Significant progress has been attained in the studies of the Upper Permian in the stratotype of the Permian System. The results of the studies conducted by many geologists and paleontologists on the Permian deposits in different regions of Russian and the CIS are generalized. The status of the traditional East-European (Biarmian) stratigraphic scale and the auxiliary regional Tethyan (near-equatorial) scale is reviewed in the light of the latest evidence. The latter scale has been widely used for subdividing the Permian deposits in the southern regions of Russia and the CIS. The advantages and disadvantages of each of the scales are considered. The boundaries of the Permian System and its series and stages of the East-European and Tethyan scales are analysed, their relationships and the possibilities of tracing are demonstrated. Correlation of the reference Permian sections in Biarmian and Tethyan realms is presented.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская